Mapping Recombination Landscape and Basidial Spore Number in the Button Mushroom Agaricus bisporus - Sonnenberg, Anton S. M.; Sedaghat-Telgerd, Narges; Lavrijssen, Brian; Hendrickx, Patrick M.; Scholtmeijer, Karin; Baars, Johan J. P.; Visser, Richard G. F.; van Peer, Arend (Frontiers in Fungal Biology, 2021)
The button mushroom Agaricus bisporus is represented mainly by two varieties, a secondarily homothallic variety with predominantly 2 heterokaryotic spores per basidia and a heterothallic variety with predominantly 4 homokaryotic spored basidia. Both varieties also differ in their recombination landscape with the former showing crossovers (CO) predominantly at chromosome ends whereas the latter has a more evenly distribution of CO over the chromosomes. The two varieties are compatible and this has been used to study segregation of the basidial spore number (BSN) and the genomic positions of recombination, i.e. the CO landscape, in order to find the underlying genetic determinants. Knowledge on genes controlling CO positions might facilitate either the conservation of favorable allele combinations or the disruption of unwanted allele combinations to reduce linkage drag. For BSN, in total 7 QTL were found with the major QTL on chromosome 1 explaining ca. 55% of the phenotypic variation. It appeared, however, difficult to map the recombination landscape. This phenotype can only be assessed in the meiotic offspring of an intervarietal hybrid which is a laborious and difficult task. Nevertheless this was done and we were able to map three QTLs for this trait, two on chromosome 1 and one on chromosome 2 not overlapping with the QTL for BSN. The hurdles encountered are discussed and a new strategy that can solve these is proposed. This new approach can be a useful strategy for a more efficient breeding strategy for mushroom in general.